Assignment of contract in forward sale of building Act in 19/1/2011 - Reza Nikkhah; seyyed salehi; Mansour Akbari Araei (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2019)
Assignment of contractual rights and obligations is one of the most important and well-known issues in different legal systems. The assignment of contract is recognized in Pre-Sale Building Act ratified in 19/1/2011. The legislator, in articles 17 and 18, specified terms and qualifications mentioned in this article. This article is based on descriptive-analytical method, and strives to discuss principles and standards in assignment contract and its justification in different legal systems. In addition, it also analyzes the assignment of contract in Pre-Sale Building Act. In this legislation, one of the most important terms known by lawmaker is the obligor’s consent for assignment in writing and official assignment. It is crucial that the legislator considered this assignment which has many economic effects and it was a great step for unification of the assignment of contract in the Act. Assignment of contract is recognized separately in uniform law as well as in laws of different countries such as France, but it has not been considered in Iran.